Effect of endocrine disruptors on bacterial virulence - Thiroux, Audrey; Berjeaud, Jean-Marc; Villéger, Romain; Crépin, Alexandre (Frontiers in Cellular and Infection Microbiology, 2023)
For several decades, questions have been raised about the effects of endocrine disruptors (ED) on environment and health. In humans, EDs interferes with hormones that are responsible for the maintenance of homeostasis, reproduction and development and therefore can cause developmental, metabolic and reproductive disorders. Because of their ubiquity in the environment, EDs can adversely impact microbial communities and pathogens virulence. At a time when bacterial resistance is inevitably emerging, it is necessary to understand the effects of EDs on the behavior of pathogenic bacteria and to identify the resulting mechanisms. Increasing studies have shown that exposure to environmental EDs can affect bacteria physiology. This review aims to highlight current knowledge of the effect of EDs on the virulence of human bacterial pathogens and discuss the future directions to investigate bacteria/EDs interaction. Given the data presented here, extended studies are required to understand the mechanisms by which EDs could modulate bacterial phenotypes in order to understand the health risks.